Carbon Monoxide Inhibits Islet Apoptosis via Induction of Autophagy - Kim, Do-Sung (Antioxid Redox Signal, 2018)
Aim: Carbon monoxide (CO) functions as a therapeutic molecule in various disease models because of its anti-inflammatory and antiapoptotic properties. We investigated the capacity of CO to reduce hypoxia-induced islet cell death and dysfunction in human and mouse models. Results: Culturing islets in CO-saturated medium protected them from hypoxia-induced apoptosis and preserved β cell function by suppressing expression of proapoptotic (Bim, PARP, Cas-3), proinflammatory (TNF-α), and endoplasmic reticulum (ER) stress (glucose-regulated protein 94, grp94, CHOP) proteins. The prosurvival effects of CO on islets were attenuated when autophagy was blocked by specific inhibitors or when either ATG7 or ATG16L1, two essential factors for autophagy, was downregulated by siRNA. In vivo, CO exposure reduced both inflammation and cell death in grafts immediately after transplantation, and enhanced long-term graft survival of CO-treated human and mouse islet grafts in streptozotocin-induced diabetic non-obese diabetic severe combined immunodeficiency (NOD-SCID) or C57BL/6 recipients. Innovation: These findings underline that pretreatment with CO protects islets from hypoxia and stress-induced cell death via upregulation of ATG16L1-mediated autophagy. Conclusion: Our results suggested that CO exposure may provide an effective means to enhance survival of grafts in clinical islet cell transplantation, and may be beneficial in other diseases in which inflammation and cell death pose impediments to achieving optimal therapeutic effects. Antioxid. Redox Signal. 28, 1309–1322.